Correlation between the Angle of the Guide Plate and Crushing Performance in Vertical Shaft Crushers - Feifei Feng; Jinfa Shi; Jie Yang; Junxu Ma (Shock and Vibration)
A geometric model of rotors is established on the basis of the structure of vertical shaft impact crusher. The dynamic simulation of the rotor is carried out by using the discrete element software EDEM. At the same time, the correlation between the angle of the guide plate and the crushing performance of the crusher is studied systematically. The optimal angle of the guide plate is obtained by theoretical analysis of the particle motion. The simulation method is used to analyze the velocity of particles, so the influence law of the angle of the guide plate on the acceleration effect of particles is obtained. The results of this paper show that the peak value of the maximum velocity of particles is the highest when the angle of the guide plate is 35°, which is consistent with the theoretical results. At this time, the average velocity of particle population is the largest and the proportion of particles with high velocity is the highest. It means that the particles obtain the largest crushing kinetic energy and the best crushing performance.